Cop killers and the death penalty: an exploratory mixed methods analysis, North Carolina (1977–2009). Issue 1 (1st January 2020) - Stewart, Bernadette; Cochran, John K.; Smith, M. Dwayne; Bjerregaard, Beth; Fogel, Sondra J.
ABSTRACT: Although all jurisdictions with capital punishment currently have at least one statutory aggravating factor for causing the death of a law-enforcement officer, little is currently known about the fate of these persons. There is a common perception that these individuals would be the most likely to receive a death sentence among those convicted of capital crimes; however, this assumption has not been empirically tested. The purpose of this research was to examine this assumption in the state of North Carolina among the population of offenders convicted of capital murder between the years of 1977 and 2009. Quantitative analysis shows that murdering a law-enforcement officer does not increase the likelihood of a death sentence. Additional qualitative analysis of these cases examines the ultimate fate of these offenders and reveals that the death penalty is reserved for those who either specifically seek out law-enforcement officers, brutalize and degrade them, or kill them in an attempt to avoid arrest or to escape that is either unsuccessful or did not require the murder to succeed in these endeavors. Implications and suggestions for future research are discussed.